Challenges and Limitations of Anti-quorum Sensing Therapies - Krzyżek, Paweł (Frontiers in Microbiology, 2019)
Abstract: Quorum sensing (QS) is a mechanism allowing microorganisms to sense population density and synchronously control genes expression. It has been shown that QS supervises the activity of many processes important for microbial pathogenicity, e.g., sporulation, biofilm formation, and secretion of enzymes or membrane vesicles. This contributed to the concept of anti-QS therapy (also called quorum quenching, QQ) and the opportunity of its application in fighting against various types of pathogens. In recent years many published articles reported promising results indicating the possibility of reducing pathogenicity of tested microorganisms and their easier eradication when co-treated with antibiotics. The aim of the present manuscript is to point to the opposite, negative side of the QQ therapy, with particular emphasis on three fundamental properties attributed to anti-QS substances: the selectivity, the virulence reduction, and the lack of resistance against QQ. This point of view may highlight new directions of research, which should be taken into account in the future before the widespread introduction of QQ therapies in the treatment of people.